Characterisation of fluid flow conditions and paths in the Buntsandstein Gp. sandstones reservoirs, Upper Rhine Graben - Bossennec Claire; Géraud Yves; Böcker Johannes; Klug Bernd; Mattioni Luca; Bertrand Lionel; Moretti Isabelle (BSGF - Earth Sciences Bulletin, 2021)
Deeply buried sandstone reservoirs are targeted in the Upper Rhine Graben (URG) for geothermal and hydrocarbon resources. These reservoirs are affected by a convective heat flow along fault zones and have a complex diagenetic and deformation history recorded in their paragenetic sequence. Here, the focus is made on siderite and barite cementation characterisation, which trace paleo geothermal circulations within the fracture network affecting the Buntsandstein Gp. sandstones. A double approach on geochemistry and fracture network features is used to characterise fluid-flow episodes in the rift basin and on its shoulders. Barite sulphur isotopic signature suggests a common source for all the locations. However, Rare Earth Elements distribution patterns, oxygen isotopic ratios, and fluid inclusion study suggest two distinct flow regimes for fluids associated with barite precipitation along the shoulders and at depth in the middle of the graben. The barite has a higher content in total REE and contains non-saline fluid inclusions on the graben shoulders, suggesting that fluid circulations within the border faults interact with sulphate rich layers and precipitate at temperature above 150 °C. In deep-seated samples from the central part of the basin, barite fluid inclusions show a wide range of salinities, suggesting a higher contribution of sedimentary brines and precipitation at lower temperatures (< 150 °C). According to their REE signature, these barite mineralisations are associated with siderite and apatite with a diagenetic source. A conceptual model for fluid circulation within the basin is built from this new dataset. Fast and deep down- and up-flows occur along the major border faults, locally leaching evaporitic horizons. A part of the infiltrated meteoric waters reaches the centre of the basin, where it then mixes with the brines in sedimentary. This new characterisation of fluid pathways in the targeted reservoir brings insights into geothermal circulation compartmentalisation at the basin scale.